Hereditary Nonsyndromic Gingival Fibromatosis: Report of Family Case Series - Syed Wali Peeran; Karthikeyan Ramalingam; Syed Ali Peeran; Marei Hamed Mugrabi; Khaled Awidat Abdulla (Case Reports in Dentistry)
Hereditary gingival fibromatosis (HGF) is a rare, benign disorder with slowly progressive enlargement of maxillary and mandibular gingiva. Herewith, we report the first case series of HGF presenting among mother and all of her 3 children. Their complaints included unaesthetic appearance due to gingival growth, malocclusion, and difficulty in mastication. Conventional gingivectomy with oral hygiene measures and regular followup is the treatment of choice for such presentation.